Wild capital : nature's economic and ecological wealth - Jones, Barbara K. (University of Florida Press, 2019)
In Wild Capital, Barbara Jones demonstrates that looking at nature through the lens of the marketplace is a surprisingly effective approach to protecting the environment. Showing that policy-makers and developers rarely associate wild places with monetary values, Jones argues that nature should be viewed as a capital asset like any other in order for environmental preservation to be a competitive alternative to construction projects.